PENGARUH PENGGUNAAN MEDIA GAMBAR DUA DIMENSI TERHADAP KEMAMPUAN MENULIS PUISI BEBAS SISWA KELAS V SD NEGERI 161 PEKANBARU - Vinessa Kanza; Otang Kurniaman; Gustimal Witri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the low ability to write free poetry for fifth grade students at SD Negeri 161 Pekanbaru. This isbecause there are still teachers who are less creative in giving lessons to students. For free poetry, two-dimensional picturemedia is a suitable for use. This research aims to determine the differences in the ability to write free poetry for studentsusing two dimensional picture media. This research method uses quasi nonequivalent control group design experiments. Thisresearch was conducted in two classes V in SD Negeri 161 Pekanbaru, namely VB as the control class and VC as theexperimental class, with each class totaling 30 students. Based on the results of the research obtained the ability to write freepoetry for students who learn using two dimensional picture media better and higher increase than students who learnwithout using learning media. It can be seen from the gain index in the experimental class using two dimensional picturemedia by 49% which is the medium category, while the gain index in the control class without using learning media is 17%which is a low category.